Change by design : how design thinking transforms organizations and inspires innovation - Brown, Tim; Katz, Barry (New York Harper Business, 2009)
Ten years later, the subject of this book, (3z(Bdesign thinking,(3y (Bis still the rage at business schools, throughout corporations, and increasingly in the popular press$1 (Bdue in large part to work of IDEO, a leading innovation and design firm. This revised and updated shows how the techniques and strategies of design have evolved and have contributed to various industries and sectors, both for profit and nonprofit.s
Keywords: Organizational change; Industrial design